CHALLENGES IN PREPARATION OF GUIDE TRANSLATORS - Alimova, Kamola (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article examines the problems in the preparation of guide-translators. High-quality training of guides and interpreters requires a developed educational program that is oriented towards modern market requirements, a competency-based approach and is capable of eliminating these contradictions. It is expected to focus on the formation of the communicative competence of the guide-translator using a foreign language. It is concluded that the excursion game “I am a tour guide” with a real visit to the museum and the use of interactive teaching methods help prepare students for future professional activities.